Genome‐Wide Association Mapping of Anthracnose (Colletotrichum sublineolum) Resistance in the U.S. Sorghum Association Panel. Issue 2 (1st July 2018) - Cuevas, Hugo E.; Prom, Louis K.; Cooper, Elizabeth A.; Knoll, Joseph E.; Ni, Xinzhi
Abstract : The productivity and profitability of sorghum [ Sorghum bicolor (L.) Moench] is reduced by susceptibility to fungal diseases, such as anthracnose ( Colletotrichum sublineolum P. Henn.). A limited number of resistant accessions are present in the temperate‐adapted germplasm; other exotic sources of resistance are not currently available for breeding programs. Among 335 accessions available to breeders from a previously genotyped sorghum association panel (SAP), we found that 75 were resistant to anthracnose. A phylogenetic analysis of these accessions showed high genetic diversity and multiple resistance sources. Genome‐wide association scans (GWAS) were conducted using 268, 289 single‐nucleotide polymorphisms to identify loci associated with anthracnose resistance. Using logistic regressions for binary measures of resistance responses, we identified three loci within a region on chromosome 5 that have been previously associated with three sources of anthracnose resistance. A GWAS limited to Caudatum germplasm identified an association with a region on chromosome 1 and with the same previous region on chromosome 5. Candidate genes within these loci were related to R‐gene families, signaling cascades, and transcriptional reprogramming, suggesting that the resistance response is controlled by multiple defense mechanisms. The strategic integration of exotic resistant germplasm into the SAP is needed to identify additional rare resistance alleles via GWAS.